Bi-ideals of a P-regular near left almost rings - Gaketem, Thtii (Asia-Pacific Journal of Science and Technology, 2017)
Bi-ideal is the generalization of quasi-ideal. In this paper, we define and study properties of bi-ideals of P- regular nLA-ring